Prevalence and morphometry of Eimeria spp in guinea pigs from Chota, Cajamarca. - Torrel Pajares, T. (2023)
This study determine the prevalence of Eimeria spp and performs the morphometricstudy of the oocysts found in the faeces of guinea pigs (Cavia porcellus) from commercialfamily-rearing farms in the district of Chota, Cajamarca, Peru. The study was conductedbetween August and October 2014. In total, 285 faecal samples were obtained regardlessof sex, age and type of guinea pigs in eight communities. The samples were processedusing the Sheather technique and the morphometric study of the oocysts was carried outby microscopic observation at 40X using a micrometric eyepiece with a correction factorof 1.64. Oocyst sporulation was induced with 2.5% potassium dichromate. The prevalenceof Eimeria spp was 25%. The average of subspherical-shaped oocysts was 17.46 μmlong and 17.25 μm wide and for ellipsoidal oocysts it was 23.40 μm long and 17.8 μm wide.The morphometric characteristics indicate that it would be Eimeria caviae.